The role of pediatric maxillary expansion on nasal breathing. A systematic review and metanalysis. (August 2020) - Calvo-Henriquez, Christian; Capasso, Robson; Chiesa-Estomba, Carlos; Liu, Stanley Yung; Martins-Neves, Silvia; Castedo, Elena; O'Connor-Reina, Carlos; Ruano-Ravina, Alberto; Kahn, Sandra
Abstract: Objective: A reduced transversal dimension of the maxilla leads to narrower nasal cavities, which may reduce airflow to the lungs. Maxillary expansion widens nasal floor. However, there is huge controversy regarding whether this increase does actually lead to increased airflow. In this systematic review and meta-analysis we aim to resolve this question by evaluating studies that have undertaken rhinomanometric measurements. Review methods: Pubmed (Medline), the Cochrane Library, EMBASE and Trip Database were checked by two authors. Two authors extracted the data. Main outcome was expressed as the difference between resistance before and after treatment and the 95% confidence interval. Results: 30 studies were selected for full text reading. A total of 12 studies (301 patients) met the inclusion criteria. All selected articles found reduced resistance after palatal expansion. The data pooled in the meta-analysis reveals a statistically significant difference of 0.12 Pa s/cm 3 mean reduction after palatal expansion (CI 95% 0.06, 0.18) for nine uncontrolled studies. Regarding nasal airflow, the pooled data show a statistically significant difference of 29.9 cm 3 /s increase after palatal expansion (CI 95% 9.17, 50.64). Conclusion: According to the available evidence, palatal expansion in pediatric patients decreases nasal resistance and increases nasal flow.